MULTIVARIATE SEQUENCE STRATIGRAPHY: TACKLING COMPLEXITY AND UNCERTAINTY WITH STRATIGRAPHIC FORWARD MODELING, MULTIPLE SCENARIOS, AND CONDITIONAL FREQUENCY MAPS - Burgess P.M.; Lammers H.; van Oosterhout C.; Granjeon D. (My University, 2006)
Sequence-stratigraphic conceptual models typically focus on accommodation as a dominant control. Although useful in many ways, this approach may not address the full range of possible controls on stratal patterns, nor is it likely to fully address uncertainty in the identification and quantification of controlling processes. Consequently, predictions from sequence-stratigraphic conceptual models may be more limited than generally stated. Progress in addressing this problem can be achieved by applying the latest generation three-dimensional stratigraphic forward modeling to (1) investigate and include more of the parameters that may control stratal architectures and (2) consider multiple scenarios to help determine the impact of uncertainty in operating processes and their parameter values. Results from a three-dimensional diffusional stratigraphic forward model illustrate this approach, suggesting that relative sea level change, shelf width, and sediment-transport efficiency are important large-scale controls on the spatial and temporal distribution of deep-marine stratal volumes. If this result is sufficiently independent of model assumptions and can be replicated in other models, it suggests that all three controlling factors should be included in interpretations and predictions of outcrop and subsurface deep-marine strata. Modeling results also suggest that combining multiple forward-model scenarios to form conditional frequency maps may be a useful, practical method to present and analyze multiple scenarios. The use of multiple forward-modeling scenarios to consider multiple controls on stratal architecture could begin to account more fully for uncertainty in controlling processes and parameter values, in sequence stratigraphy generally, and evaluation of subsurface uncertainty specifically. Copyright © 2006. The American Association of Petroleum Geologists. All rights reserved.